Pengaruh Budaya Organisasi, Lingkungan Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan - Andre Afriadi; Hadi Sunaryo; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to describe the variables of Organizational Culture, Work Environment, Job Satisfaction and Employee Performance of PT. Blambangan Foodpackers Indonesia (BFPI), to determine the influence of the variables of Organizational Culture, Work Environment and Job Satisfaction on Employee Performance. This research was conducted at PT. Blambangan Foodpackers Indonesia (BFPI) with a sample size of 73 respondents. The data analysis technique uses multiple linear regression analysis. Descriptive analysis results show that employees of PT. Blambangan Foodpackers Indonesia (BFPI) agreed on all research variables, namely Organizational Culture, Work Environment, Job Satisfaction and Employee Performance. Organizational Culture and Job Satisfaction have a significant effect on Employee Performance. The work environment has no significant effect on employee performance. Organizational Culture, Work Environment and Job Satisfaction simultaneously have a significant effect on Employee Performance at PT. Blambangan Foodpackers Indonesia (BFPI). Keywords: Organizational Culture, Work Environment, Job Satisfaction and                        Performance Employees